Project-Based Learning in Mathematics Classrooms: How It Improves Students' Problem-Solving Skills - Purnomo, Heri; Abdullah, Abdul Halim; Afnia, Pangestika Nur; Shiddieqy, Abdullah Ash (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
The aim of this research is to determine whether Project-Based Learning (PjBL) affects middle school students' ability to solve mathematical problems during the learning process. This research is mix-method research with explanatory sequential design, namely the data is analyzed quantitatively first and continued with descriptive qualitative analysis. The results of the test indicated a t-value of 2.7354 with a p-value of 0.007751 (which is less than 0.05), signifying a significant difference of the experimental group and the control group after the treatment was applied. PjBL has an influence in improving problem solving of middle school students. Students can identify important elements in a problem, create appropriate problem representations, use relevant knowledge and skills to solve problems, and are able to interpret relevant results and conclusions. This study suggests that PjBL provides an impact on meaningful learning experiences and in-depth learning.